The unruly city Paris, London and New York in the age of revolution - Rapport, Michael (Basic Books, 2017)
"A vivid history of three intertwined cities--Paris, London, and New York--at the turn of the nineteenth century, in the midst of political chaos. From the British occupation of New York during the Revolutionary War, to agitation for democracy in London, to popular uprisings and regicide in Paris, Rapport explores the relationship between city and revolution, revealing why some cities engender upheaval and some suppress it. Why did Paris experience a devastating revolution while London avoided one? How did American independence spark activism in cities across the Atlantic? And how did these cities influence the development of modern democracy? Rapport takes readers from the politically charged taverns and coffeehouses on Fleet Street, through a sea battle between the British and French in New York Harbor, to the scaffold during the 'Terror' in Paris. Drawing on letters, travelogues and eye-witness accounts, Rapport evokes the sights, sounds and smells of these cities, masterfully weaving their history with the politics of revolution."--Jacket.